A note to my paper “Multi-algebras from the viewpoint of algebraic logic” - Cırulis, J. (Algebra and Discrete Mathematics, 2004)
The definition of a resolvent, introduced in the
paper mentioned in the title, is simplified, and some misprints in
that paper are corrected.